Nos domínios de Eros: o Simbolismo Singular de Gilka Machado - Nunes, Fernanda Cardoso (2007)
The beginning of the 20th Century found Brazilian literature inside a changing stage where several literary aesthetic, including Symbolism, were living together varying between the tradition and the renovation. The work of Gilka Machado (1893-1980) arises in this changing stage and it provoked public and criticism scandals. Her first books, Cristais partidos (Broken crystals) (1915) and Estados de alma (States of mind) (1917), revolutionized Brazilian feminine poetry. Her verses were full of a transcendent and sensual erotism that shocked her epoch because they broke the conventional women’s social profile. It made her an unknown poet. Aiming to rediscover a poet who was acclaimed as the best Brazilian feminine poet, we will try to analize her work’s aspects wich made her pioneerism and originality. At a first moment, we will try to place her work inside the Brazilian literature history and her link with the Symbolism and the Syncretic literary period. Besides, we investigate her participation in Festa magazine literary group. After this, we analize her link with the historical-cultural context. Her poetry denounced the Brazilian women unfavorable conditions and the slow process carried out by other women writers who aimed to write at that epoch. Gilka Machado exceeds the social and cultural limits and brings about a re-evaluation of the women’s role in Brazilian literature and society. She suffered reprisal due of her daring. In order to verificate how this repression affected her work, we proceed a criticism revision. In a third moment, we analize the erotic phenomenon in her work and how this phenomenon awards her a singular part in the Brazilian Symbolism. We investigate how the erotic writing, until this moment forbidden to women writers, will be a definiting and inovating characteristic of her poetry. It represents her poetry integrating force and it will follow several directions: the Nature, the lover body and the lower classes. We aim to help rediscovering and rescuing this poet that broke established social and literary rules and dared to sing her own body with freedom.